The English Anthems - Byrd, William 1539/40-1623; Monson, Craig A.; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1983)
The composition of Anglican church music was never one of Byrd’s priorities, but his anthems on English texts remained in favour long after his death, and for two centuries were the works by which his name was remembered. Full and verse anthems are included in this volume, with anthems from secular sources and fragmentary and doubtful works also collected.
Keywords: 16th Century (1501-1600); Anthem